Swarm Intelligence and its Application in Abnormal Data Detection - Liu, Bo; Cai, Mei; Yu, Jiazong (Informatica, 2015)
This study addresses swarm intelligence-based approaches in data quality detection. First, three typicalswarm intelligence models and their applications in abnormity detection are introduced, including AntColony Optimization (ACO), Particle Swarm Optimization (PSO), Bee Colony Optimization (BCO).Then, it presents three approaches based on ACO, PSO and BCO for detection of attribute outliers indatasets. These approaches use different search strategies on the data items; however, they choose thesame fitness function (i.e. the O-measure) to evaluate the solutions, and they make use of swarms of thefittest agents and random moving agents to obtain superior solutions by changing the searching paths orpositions of agents. Three algorithms are described and explained, which are efficient by heuristicprinciples.